THE ROLE OF FINANCIAL TECHNOLOGY (FINTECH) IN BUILDING AN INCLUSIVE ECONOMY 5.0 - Caroline Caroline (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Financial Technology (Fintech) has great potential in building an inclusive Economy 5.0 by expanding access to financial services to previously underserved communities. Through innovations in digital payments, peer-to-peer lending, and automated investment management, Fintech is able to provide faster, safer, and more efficient financial solutions. This contributes to economic equality and the empowerment of individuals and small businesses. In addition, collaboration between the Fintech sector and the traditional financial sector, with support from various stakeholders, is essential to overcome regulatory and data security challenges. Thus, Fintech can be the main driving force for a more inclusive, fair, and sustainable economic transformation.